OPTIMIZATION OF TREATMENT OF ATYPICAL PNEUMONIA DUE TO HYPOXIC-ISCHEMIC ENCEPHALOPATHY IN NEWBORNS - Ibragimova Marina Fedorovna; Esanova Munira Ravshanovna (Research Focus International Scientific Journal, 2024)
Acute respiratory pathology occupies a leading place in the structure of morbidity in children. The leading place among them belongs to pneumonia, which is characterized by a high prevalence in the early age group, severity of the course, and the possibility of transition to severe forms. The purpose of the study is to develop new systems for complex therapy and rehabilitation of newborns with atypical pneumonia against the background of hypoxic-ischemic encephalopathy. Materials and methods of research: Group I – 40 children who received traditional treatment, of which 28 had a moderate-severe form and 12 had a severe form. Group II – 45 children who received, in addition to traditional treatment, cytochrome C, immunomodulin and of these, 32 are moderately severe and 13 are severe.